2008
DOI: 10.1016/j.ica.2007.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of structurally-related alkoxide, amine, and thiolate-ligated MII (M=Fe, Co) complexes: The influence of thiolates on the properties of biologically relevant metal complexes

Abstract: Mechanistic pathways of metalloenzymes are controlled by the metal ion's electronic and magnetic properties, which are tuned by the coordinated ligands. The functional advantage gained by incorporating cysteinates into the active site of non-heme iron enzymes such as superoxide reductase (SOR) is not entirely understood. Herein we compare the structural and redox properties of a series of structurally-related thiolate, alkoxide, and amine-ligated Fe(II) complexes in order to determine how the thiolate influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…One equivalent of TEMPOH was required for complete disappearance of 7 (Figure S-24) or 8 (Figure S-23) indicating that a clean 1:1 stoichiometric reaction is involved. The initial products expected in these reactions [Mn II (S Me2 N 4 (tren))(ROH)] + (R= H, Me) are not observed, consistent with the electrochemical data ( vide supra ; Figures S-13 - S-14) which demonstrates that these six-coordinate reduced species are unstable 52,57 on the time-scale of these experiments. Phenoxide-bound 5 and 6 show no reaction with TEMPOH, even when excess substrate is added and the reaction mixture is monitored for prolonged periods under anaerobic conditions (~24 hrs).…”
Section: Resultssupporting
confidence: 85%
“…One equivalent of TEMPOH was required for complete disappearance of 7 (Figure S-24) or 8 (Figure S-23) indicating that a clean 1:1 stoichiometric reaction is involved. The initial products expected in these reactions [Mn II (S Me2 N 4 (tren))(ROH)] + (R= H, Me) are not observed, consistent with the electrochemical data ( vide supra ; Figures S-13 - S-14) which demonstrates that these six-coordinate reduced species are unstable 52,57 on the time-scale of these experiments. Phenoxide-bound 5 and 6 show no reaction with TEMPOH, even when excess substrate is added and the reaction mixture is monitored for prolonged periods under anaerobic conditions (~24 hrs).…”
Section: Resultssupporting
confidence: 85%
“…Previously we, and others, showed that gem dimethyls adjacent to the sulfur can prevent dimerization of iron thiolates 18,21,50-52. And more recently we showed that thiolate ligands reduce metal ion Lewis acidity relative to alkoxides and amines, and have a strong trans influence thereby helping to maintain an open coordination site 53. The previously reported tame-N 3 (1,1,1-triaminoethane)54,55 ligand was used in this study as a scaffold for the new complexes, since it favors a more open, less constrained, square pyramidal or octahedral geometry as illustrated in Scheme 1.…”
Section: Resultsmentioning
confidence: 87%
“…The thiolate ligand helps to maintain an open coordination site. 94 O 2 binding to 1 is found to be relatively slow compared to related biologically relevant Fe and Cu complexes. In the absence of any other kinetic data for O 2 binding to Mn(II), it would be difficult to draw any conclusions regarding the role of the metal ion in this reaction.…”
Section: Discussionmentioning
confidence: 90%